2004
DOI: 10.1086/422355
|View full text |Cite
|
Sign up to set email alerts
|

The Density of Coronal Plasma in Active Stellar Coronae

Abstract: We have analyzed high-resolution X-ray spectra of a sample of 22 active stars observed with the High Energy Transmission Grating Spectrometer on {\em Chandra} in order to investigate their coronal plasma density. Densities where investigated using the lines of the He-like ions O VII, Mg XI, and Si XIII. While Si XIII lines in all stars of the sample are compatible with the low-density limit, Mg XI lines betray the presence of high plasma densities ($> 10^{12}$ cm$^{-3}$) for most of the sources with higher X-r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
137
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(157 citation statements)
references
References 83 publications
19
137
1
Order By: Relevance
“…This value is compatible with density diagnostics from line ratios of hot He-like triplets, such as Mg xi, observed during flaring and quiescence on II Peg (Huenemoerder et al 2001;Testa et al 2004). Similarly high densities have also been reported by Güdel et al (2002) during an X-ray flare in Proxima Centauri.…”
Section: Plasma Density Volume and Loop Cross-sectional Areasupporting
confidence: 89%
“…This value is compatible with density diagnostics from line ratios of hot He-like triplets, such as Mg xi, observed during flaring and quiescence on II Peg (Huenemoerder et al 2001;Testa et al 2004). Similarly high densities have also been reported by Güdel et al (2002) during an X-ray flare in Proxima Centauri.…”
Section: Plasma Density Volume and Loop Cross-sectional Areasupporting
confidence: 89%
“…These arguments are qualitative, and we have insufficient spectroscopic diagnostic information to investigate abundance variations with temperature in a rigorous fashion. We note, however, that such abundance variations might not be unreasonable in the light of a recent survey of coronal densities by Testa et al (2004) that clearly demonstrates that the cooler T $ 10 6 K corona resides in quite different structures to the hotter, T $ 10 7 K plasma that appears to be universally characterized by much higher pressures. Feldman & Laming (2000) found that for the solar corona the FIP effect is larger at T $ 10 5:9 K than at T $ 10 6:15 K.…”
Section: Temperature Structurementioning
confidence: 58%
“…We also computed synthetic spectra using emissivities from the APED database ) and the DEM and abundances derived from line set 1 for comparison. For these simulations, we have use an electron density of n e ¼ 5 ; 10 11 cm À3 for AB Dor and n e ¼ 2 ; 10 10 cm À3 for V471 Tau (Testa et al 2004), with an interstellar medium column density of n H ¼ 1 ; 10 18 cm À2 . The exact density and very low ISM column make no practical difference to the synthetic spectra.…”
Section: Resultsmentioning
confidence: 99%
“…This component could be produced by the shock-heated plasma at the base of the accretion column, the plasma density being much higher than that (n e ≤ 10 10 cm −3 ) measured for coronae of active stars (Testa et al 2004). The discovery of optical depths effects on the X-ray spectrum of MP Mus further supports this hypothesis (Argiroffi et al 2009).…”
Section: Introductionmentioning
confidence: 70%